2016
DOI: 10.1111/ics.12355
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary performance data of the RHE/IL‐18 assay performed on SkinEthicRHE for the identification of contact sensitizers

Abstract: The prediction model to be used was refined, and more substances have to be tested in order to gather enough data for this evaluation and to determine the right criteria applicable for this assay using the SkinEthic RHE test system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…IL-18 has proven to be a relevant biomarker for assessing sensitizing potential of chemicals in in vitro assays. [25][26][27] An expanded study with the RHE model showed that exposure to known sensitizing metal salts, such as potassium dichromate, chromium(III) chloride, nickel(II) chloride hexahydrate, nickel(II) sulfate hexahydrate, gold(I) chloride, sodium aurothiosulfate(I), cobalt(II) chloride, mercuric(II) chloride, and copper(II) sulfate, in contrast to chemical sensitizers, resulted in no increase or only a small increase in IL-18 production in RHE. 18 Specifically, the four titanium salts, namely, titanium(IV) isopropoxide, titanium(IV) bis(ammonium lactate) dihydroxide (TiALH), titanium(IV) oxide, and calcium titanate that were tested failed to result in an increase in IL-18 release into the culture medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-18 has proven to be a relevant biomarker for assessing sensitizing potential of chemicals in in vitro assays. [25][26][27] An expanded study with the RHE model showed that exposure to known sensitizing metal salts, such as potassium dichromate, chromium(III) chloride, nickel(II) chloride hexahydrate, nickel(II) sulfate hexahydrate, gold(I) chloride, sodium aurothiosulfate(I), cobalt(II) chloride, mercuric(II) chloride, and copper(II) sulfate, in contrast to chemical sensitizers, resulted in no increase or only a small increase in IL-18 production in RHE. 18 Specifically, the four titanium salts, namely, titanium(IV) isopropoxide, titanium(IV) bis(ammonium lactate) dihydroxide (TiALH), titanium(IV) oxide, and calcium titanate that were tested failed to result in an increase in IL-18 release into the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, we have developed a reconstructed human epidermis (RHE) model to identify contact sensitizers from nonsensitizers and assess sensitizer potency 25 by measuring IL‐18 release into the culture medium after topical exposure of chemicals to the stratum corneum. IL‐18 has proven to be a relevant biomarker for assessing sensitizing potential of chemicals in in vitro assays 25‐27 . An expanded study with the RHE model showed that exposure to known sensitizing metal salts, such as potassium dichromate, chromium(III) chloride, nickel(II) chloride hexahydrate, nickel(II) sulfate hexahydrate, gold(I) chloride, sodium aurothiosulfate(I), cobalt(II) chloride, mercuric(II) chloride, and copper(II) sulfate, in contrast to chemical sensitizers, resulted in no increase or only a small increase in IL‐18 production in RHE 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The rhe/IL-18 assay was performed following previously described process Andres et al 26 Briefly, the test systems (reconstructed epidermises) were exposed to the test items, then, after a defined period of exposure, the release of IL-18 cytokine and the viability of the tests systems were evaluated by ELISA and MTT assays, respectively. The results from both tests were combined to classify the test items following predefined prediction models described in this paper.…”
Section: Rhe/il-18 Assaymentioning
confidence: 99%
“…Several types of reconstructed Human epidermis (rhe) have been evaluated for their suitability for the IL-18 assay. 25,26 The assay has been proven to be reliable when performed on 3 commercially available rhe models and one from the Amsterdam university (EpiDERM TM , EpiCS TM , RHE TM and VUMC-EE respectively). Although these reconstructed human epidermises were at first designed for skin corrosion and irritation testing, it is not surprising that they respond to skin sensitisers by releasing specific pro-inflammatory cytokines, since the majority of skin sensitisers are also skin irritants.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different factors produced by KCs, IL‐18 has been shown to play a key proximal role in the induction of allergic contact sensitization (Antonopoulos et al., ; Okamura et al., ), and recent evidence provided from our group, has shown that IL‐18 production in human KCs (NCTC 2544) can be used as a sensitive method to identify contact allergens, discriminating them from respiratory allergens and irritants, with a sensitivity of 87%, specificity of 95% and an accuracy of 90% (Corsini et al., , ; Galbiati et al., ). Replacing NCTC 2544 cell line with a standardized commercially available reconstituted human epidermis (RhE), as described in our previous manuscript (Gibbs et al., ), made the assay extremely transferable and easy to perform (Andres et al., ; Teunis et al., ).…”
Section: Commentarymentioning
confidence: 99%